STRATEGI BELAJAR YANG TERCERMIN DALAM KESALAHAN INTERLANGUAGE SISWA MAN I SURAKARTA - Darussalam, Hanif Maghruf; Fauziati, Endang (Jurnal Penelitian Humaniora, 2015)
The current study concerns learning strategy and its relation to interlanguage  errors as Selinker believes that interlanguage errors are the result of cognitive mechanism or learning strategy used by second language learner. This specifically tries to describe the learning strategy used by the learners which result in interlanguage errors. The data are in the form of sentences containing errors taken from students? compositions. The technique used to collect the data is elicitation and documentation. The data were analyzed qualitatively. The result of the research indicates that there are three major types of learning strategy used by the learners, namely: overgeneralization, first language transfer, and simplification and the dominant learning strategy is overgeneralization. This implies that the students have relied more on their linguistic knowledge on the target language (English) rather than on that of their first language. The pedagogical implication is that English teachers should have positive attitude on interlanguage errors since errors are inevitable process in foreign language learning. They must also provide appropriate training so that students are aware the differences between English and Indonesian. Such an understanding may help them eliminate the interlanguage errors and develop their interlanguage system.